Effect of animated video-based education on mothers’ skills in the early detection of growth and development in children aged 1–5 years - Wahyuni, Sri Wahyuni; budiyati, arum budiyati; Musdalifah, Ulfah Musdalifah (Universitas Muhammadiyah Purwokerto, 2026)
Background: Early childhood is a critical period for growth and development, during which delays in motor and developmental domains remain common. In Indonesia, a considerable proportion of children experience developmental disorders, partly due to limited parental knowledge and suboptimal early stimulation practices. Animated video-based education can enhance learning by delivering information through engaging visual and auditory formats. Purpose: This study aimed to examine the effect of animated video-based education on mothers’ skills in the early detection of growth and development in children aged 1–5 years. Method: A quasi-experimental study with a one-group pretest–posttest design was conducted at Pudakpayung Health Center, Semarang. A total of 33 mothers with children aged 1–5 years were selected using simple random sampling from a population of 93 respondents. Participants received a 10-minute animated video on early detection of child growth and development. Mothers’ skills were assessed using an observation checklist before and two days after the intervention. Data were analyzed using a paired sample t-test. Results: The mean score of early detection skills increased from 75.88 (pretest) to 85.88 (posttest), indicating an improvement of 10 points. Paired sample t-test analysis showed a statistically significant difference after the intervention (p = 0.003). Conclusion: Animated video-based education significantly improves mothers’ skills in the early detection of child growth and development. This approach may serve as an effective educational strategy in community health settings to enhance early detection practices.